Regional Design - Verena Balz (A+BE: Architecture and the Built Environment)
In the 1980s, planning approaches in European regions have changed as a result of increasing attention to regional spatial developments and a diminishing reliance on government-led statutory planning schemes. Emerging new approaches, often called spatial planning, shifted the focus from planning predefined territories to the planning of spatial networks, which stretch across multiple administrative boundaries. In this specific context of spatial planning, new decision-making approaches have emerged, involving coalitions of plan actors from multiple tiers and levels of government as well as market and civil actors. In near absence of formally approved statutory planning frameworks, broad involvement became a way to legitimize planning decisions and, at the same time, amass organisational capacity for their implementation.